2013
DOI: 10.1177/1541931213571189
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intellegence and Decision Making Under Stress

Abstract: This study investigated the protective effects of emotional intelligence (EI) during decision-making under stress. The researchers assigned 172 participants to either a negative or neutral feedback group and assessed EI, distress, information search prior to choice, and decision-making performance. We predicted EI would be associated with superior decision-making following negative performance feedback. Statistical analysis revealed negative feedback significantly increased distress and was associated with poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Webb et al ( 2014 ) also found a positive correlation between the IGT and MSCEIT total scores and the “facilitating” and “understanding” branches, although they found that EI did not significantly predict the variance of the decision-making task beyond the IQ (cognitive intelligence) scores. In two other studies (which used the simulated arctic rescue scenario and the SJT), Fallon et al ( 2013 , 2014 ) did not find any differences between high- and low-EI participants in their cognitive performance, although Fallon et al ( 2014 ) discovered a tendency for EI to correlate with accuracy. Alkozei et al ( 2015 ), using the airport decision-making task mentioned previously, found that higher EI (measured by the MSCEIT) achieved better performance than lower EI in the cognitive task, especially those with higher scores in the “understanding” and “facilitating” branches.…”
Section: Resultsmentioning
confidence: 95%
“…Webb et al ( 2014 ) also found a positive correlation between the IGT and MSCEIT total scores and the “facilitating” and “understanding” branches, although they found that EI did not significantly predict the variance of the decision-making task beyond the IQ (cognitive intelligence) scores. In two other studies (which used the simulated arctic rescue scenario and the SJT), Fallon et al ( 2013 , 2014 ) did not find any differences between high- and low-EI participants in their cognitive performance, although Fallon et al ( 2014 ) discovered a tendency for EI to correlate with accuracy. Alkozei et al ( 2015 ), using the airport decision-making task mentioned previously, found that higher EI (measured by the MSCEIT) achieved better performance than lower EI in the cognitive task, especially those with higher scores in the “understanding” and “facilitating” branches.…”
Section: Resultsmentioning
confidence: 95%
“…In the face of the disruptions to supply chains and panic buying associated with the pandemic, the pre-pandemic condom accessibility issue may have become compounded, thereby increasing the likelihood of condomless sex during the pandemic and the risks of the spread of infections. Third, stressors [47], including COVID-19 pandemic-related stress [48], affect decision making, resulting in poor and impulsive decisions [49,50] that may impact condom use. Moreover, the possibility of mixing sex with alcohol while seeking relief from mental health distress, as indicated during the interviews, could also impair decisions to make safer sex-related choices as alcohol may impair the condom use decision [32].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in line with this, Alkozei, Schwab, and Killgore (2016) have shown that individuals with higher levels of ability EI, but not trait EI, are more likely to utilize relevant facial features when presented with photographs during the performance of an emotional decision-making task. In addition, individuals with higher levels of ability EI also perform faster on social exchange problems (Reis et al, 2007), and were observed to display greater performance on a simulated arctic rescue scenario task that included high levels of stress (Fallon, Matthews, Panganiban, Wohleber, & Roberts, 2013;Fallon et al, 2014). While the majority of these studies suggest that ability EI is a better predictor of success on emotional decision-making tasks than trait EI, one study did show that higher levels of trait EI were positively associated with the ability to ignore irrelevant facial cues during a social gambling task (Telle, Senior, & Butler, 2011).…”
Section: The Role Of Ei In Emotional Decision-makingmentioning
confidence: 99%